2017
DOI: 10.15171/joddd.2017.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of repeated preheating of dimethacrylate and silorane-based composite resins on marginal gap of class V restorations

Abstract: Background. One of the problems with composite resin restorations is gap formation at resin‒tooth interface. The present study evaluated the effect of preheating cycles of silorane- and dimethacrylate-based composite resins on gap formation at the gingival margins of Class V restorations.Methods. In this in vitro study, standard Class V cavities were prepared on the buccal surfaces of 48 bovine incisors. For restorative procedure, the samples were randomly divided into 2 groups based on the type of composite r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this context, Fores-Salgado et al ( 13 ) and Elsayad ( 14 ) reported better adaptation and lower marginal gaps with preheating of composite resins. In a study by Alizade Oskoee et al , the formation of gaps at the gingival margins of Cl V cavities decreased with the preheating technique ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, Fores-Salgado et al ( 13 ) and Elsayad ( 14 ) reported better adaptation and lower marginal gaps with preheating of composite resins. In a study by Alizade Oskoee et al , the formation of gaps at the gingival margins of Cl V cavities decreased with the preheating technique ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preheating time varied significantly from 20 s to 1 h; 5 min 3,11,15,20 ( n = 4), 15 min 13,29,36,41 ( n = 4), and 10 min 21,23,35 ( n = 3) were the most frequently reported. Microhardness 3,14,16,17,21,27,34,36,40,44 ( n = 10) was the most assessed property, followed by marginal adaptation 20,23–25,29,37,42,43,45 ( n = 9), conversion degree 13,15,19,24,28,34,46–48 ( n = 9), and flexural strength 18,21,24,26,35,36,39,41,42 ( n = 9). Scanning electron microscopy 20,24,25,42,43 ( n = 5) was the most used marginal adaptation measurement, followed by stereomicroscopy 23,45 ( n = 2) and confocal microscopy 25 ( n = 1), digital microscopy 29 ( n = 1), and optical microscopy 37 ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…The parameters least described in the methodology were operator blinding and sample size calculation. Most studies were classified as medium risk of bias 3,11–15,17,19,21,24,26,29,30,36,37,39,41,45,46,48,50 ( n = 21), followed by low 16,20,23,25,27,28,33–35,39,43,47 ( n = 13) and high risks 18,22,44,46,49 ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Pre-heating was performed using warm bath equipped with thermostatic control (TELEDYNE HANAU, Buffalo, NY, USA). The material temperature was measured using digital microprobe GBC KDM 350, KON (EL CO SPA, Milano, Italy) ( 11 ). The heating time was 5 minutes based on the pilot study.…”
Section: Methodsmentioning
confidence: 99%